2008
DOI: 10.1159/000135707
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of N-Acetylcysteine and Ischemic Preconditioning in a Canine Model of Hepatic Ischemia-Reperfusion Injury

Abstract: Aims: We evaluated the possibility that repeated ischemic preconditioning or N-acetylcysteine (NAC) could prevent ischemia-reperfusion injury as determined by indocyanine green plasma disappearance rate (ICG-PDR) or has favorable hemodynamic effects during reperfusion in an in vivo canine liver model. Methods: Under general anesthesia, 3 groups of mongrel dogs (n = 5 per group) were subjected to (1) 60-min hepatic ischemia, (2) same ischemia preceded by intravenous administration of 150 mg kg–1 NAC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(21 reference statements)
0
13
0
1
Order By: Relevance
“…Galhardo et al [14] found that 150 mg/kg IV NAC administration to rats before hepatic ischemia, reduced necrosis, apoptosis, and microvesicular steatosis compared to IR group. But controversial to these findings Ghosh et al [30] and Baumann et al [31] could not show the beneficial effects of 150 mg/kg IV NAC before hepatic ischemia.…”
Section: Discussionmentioning
confidence: 95%
“…Galhardo et al [14] found that 150 mg/kg IV NAC administration to rats before hepatic ischemia, reduced necrosis, apoptosis, and microvesicular steatosis compared to IR group. But controversial to these findings Ghosh et al [30] and Baumann et al [31] could not show the beneficial effects of 150 mg/kg IV NAC before hepatic ischemia.…”
Section: Discussionmentioning
confidence: 95%
“…12 I/R injury is a common phenomenon in liver transplantation and resection, with morbidity and mortality as complications. 15,16 During liver transplantation, ischemic damage occurs when blood flow is cut off to the donating liver, and the injury is further intensified when the liver is transplanted into the recipient. 17 The reason for reperfusion injury is the reintroduction of oxygenated blood, which results in oxidative stress, causing increased microvascular permeability, intracellular ATP loss, inflammatory cell infiltration, and, potentially, cell death.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuing shortage of available donor livers, the increased use of extended criteria donor grafts further increases IRI, adversely affecting both short‐term and long‐term outcomes of graft and patient survival 4‐6. Numerous studies have investigated the benefits of pharmacological, heat shock, and ischemic preconditioning (IPC) interventions aimed at decreasing liver IRI 7‐13. Among them, IPC remains the most studied with a nearly uniform protective benefit in animal liver transplantation models with improved survival and decreased IRI 8, 14‐17.…”
mentioning
confidence: 99%